Distributing Agency and Experience in Therapeutic Interaction: Person References in Therapists' Responses to Complaints - Etelämäki, Marja; Voutilainen, Liisa; Weiste, Elina (Frontiers in Psychology, 2021)
The primary means for psychotherapy interaction is language. Since talk-in-interaction is accomplished and rendered interpretable by the systematic use of linguistic resources, this study focuses on one of the central issues in psychotherapy, namely agency, and the ways in which linguistic resources, person references in particular, are used for constructing different types of agency in psychotherapy interaction. The study investigates therapists’ responses to turns where the client complains about a third party. It focuses on the way therapists’ responses distribute experience and agency between the therapist and the client by comparing responses formulated with the zero-person (a formulation that lacks a grammatical subject, that is, a reference to the agent) to responses formulated with a second person singular pronoun that refers to the client. The study thus approaches agency as situated, dynamic and interactional: an agent is a social unit whose elements (flexibility and accountability) are distributed in the therapist-client interaction. The data consist of 70 audio-recorded sessions of cognitive psychotherapy and psychoanalysis, and the method of analysis is conversation analysis and interactional linguistics. The main findings are that therapists use the zero-person for two types of responses: affiliating and empathetic responses that distribute the emotional experience between the client and the therapist, and responses that invite clients to interpret their own experiences, thereby distributing control and responsibility to the clients. In contrast, the second person references are used for re-constructing the client’s past history. The conclusion is that therapists use the zero-person for both immediate emotional work and interpretative co-work on the client’s experiences. The study suggests that therapists’ use of the zero-person does not necessarily attribute “weak agency” to the client but instead might strengthen the clients’ agency in the sense of control and responsibility in the long term.